Burnout e estressores ocupacionais durante a pandemia do Covid-19: avaliação de professores da educação básica - Andrade, Lindinalva de Souza (2022)
The Covid-19 pandemic had a huge impact on society, not only in terms of health vulnerability, but in routines changes, in a context of social and work relationships, which required safety measures and social distancing. Different professional categories had to migrate and adapt themselves to remote work, which had an impact on the physical and psychological health of workers. Research indicates that among the professionals most impacted at this moment are those in the health and education area. Education professionals, especially teachers, needed to reinvent themselves in a short period of time, incorporating information and communication technologies into their work routine, in addition to the pedagogical adaptations necessary for remote/hybrid classes to take place. In this context, reports of sick teachers and, with behavioral and emotional changes, reaching diagnoses of stress, anxiety and burnout. This study sought to evaluate the stress in the dimension of exhaustion and burnout faced by teachers of the municipal and state education network in the Municipality of Araputanga - MT, during the Covid-19 pandemic. Were also compared the patterns of sick leave of teachers before and during the pandemic. The study of a descriptive nature, involved the application of three instruments in 102 teachers who remained in professional activity during the pandemic: Sociodemographic questionnaire; Jbeili Questionnaire, to preliminary identification of burnout, and Teachers' Perception of Occupational Stressors Scale (EPEOP). In addition, information was collected in the database of the Municipal Secretary of Education and State Pedagogical Advisory for Education that identified the quantity, period and reasons for the absence of teachers on average leave before and during the pandemic. A greater number of teachers on leave during the pandemic and a higher incidence of mental health leaves were identified, compared to general health, in both periods. With regard to burnout rates, 47.1% of the 102 teachers are in the “initial stage of burnout” and 24.5% with “the possibility of developing burnout”. The “working hours” and “physical and environmental aspects of work” were the occupational stressors most frequently mentioned by the participants. It was concluded that it is important to invest in prevention actions in the social, physical and psychological aspects, understanding that teacher illness is often related to working conditions. Thus, preventive actions should focus on improving the environment and working conditions so that they do not impact the teacher's health, leading to sick leave.